2022
DOI: 10.21203/rs.3.rs-1590684/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular screening of the landraces from Turkey and modern bread wheat cultivars for HMW-GS, wbm, waxy genes and Lr34 gene

Abstract: Landraces are significant genetic resources for wheat breeding as they can adapt to their regions of origin. However, for this genetic resource to be used effectively in wheat breeding, it should be screened molecularly for some functional genes. The study used 123 landraces and modern bread wheat varieties grown in Turkey. We screened the genetic materials for the wbm , waxy genes, High Molecular Weight Glutenin Subunits (HMW-GS), and the Lr34 gene, which provides adult plant resistance to rust disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Previous research showed that 2 + 12 subunits of Glu-D1 site associated with gluten titers were the most common subunit in 123 regional varieties and modern bread wheat varieties, accounting for 63.4%, and 5 + 10 subunits associated with strong gluten bread wheat were found in 22 wheat varieties, accounting for 17.8%. Apart from these two subunits, 2.1 + 12, 2 + 12′, and 2 + 12* subunits were also found among the varieties (Sönmez et al, 2023).…”
Section: Effects Of Grain Hardness Genes On Quality Traitsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous research showed that 2 + 12 subunits of Glu-D1 site associated with gluten titers were the most common subunit in 123 regional varieties and modern bread wheat varieties, accounting for 63.4%, and 5 + 10 subunits associated with strong gluten bread wheat were found in 22 wheat varieties, accounting for 17.8%. Apart from these two subunits, 2.1 + 12, 2 + 12′, and 2 + 12* subunits were also found among the varieties (Sönmez et al, 2023).…”
Section: Effects Of Grain Hardness Genes On Quality Traitsmentioning
confidence: 93%
“…Each site produces two subunits, named as x and y subunits (Zhang et al, 2016). The highquality subunits, namely, Ax1 or Ax2*(1/2*), Dx5+Dy10 (5 + 10) and their combinations have a positive effect on the strength of gluten (Payne, 1987;Cooper et al, 2015;Vancini et al, 2019;Guzmán et al, 2022;Sönmez et al, 2023).…”
Section: Open Access Edited Bymentioning
confidence: 99%